Effectiveness of ready-to-use therapeutic food compared to a corn/soy-blend-based pre-mix for the treatment of childhood moderate acute malnutrition in Niger. - Nackers, F; Broillet, F; Oumarou, D; Djibo, A; Gaboulaud, V; Guerin, P; Rusch, B; Grais, R; Captier, V (2010)
Standard nutritional treatment of moderate acute malnutrition (MAM) relies on fortified blended flours though their importance to treat this condition is a matter of discussion. With the newly introduced World Health Organization growth standards, more children at an early stage of malnutrition will be treated following the dietary protocols as for severe acute malnutrition, including ready-to-use therapeutic food (RUTF). We compared the effectiveness of RUTF and a corn/soy-blend (CSB)-based pre-mix for the treatment of MAM in the supplementary feeding programmes (SFPs) supported by Médecins Sans Frontières, located in the Zinder region (south of Niger). Children measuring 65 to <110 cm, newly admitted with MAM [weight-for-height (WHM%) between 70% and <80% of the NCHS median] were randomly allocated to receive either RUTF (Plumpy'Nut®, 1000 kcal day(-1)) or a CSB pre-mix (1231 kcal day(-1)). Other interventions were similar in both groups (e.g. weekly family ration and ration at discharge). Children were followed weekly up to recovery (WHM% ≥ 85% for 2 consecutive weeks). In total, 215 children were recruited in the RUTF group and 236 children in the CSB pre-mix group with an overall recovery rate of 79.1 and 64.4%, respectively (p < 0.001). There was no evidence for a difference between death, defaulter and non-responder rates. More transfers to the inpatient Therapeutic Feeding Centre (I-TFC) were observed in the CSB pre-mix group (19.1%) compared to the RUTF group (9.3%) (p = 0.003). The average weight gain up to discharge was 1.08 g kg(-1) day(-1) higher in the RUTF group [95% confidence interval: 0.46-1.70] and the length of stay was 2 weeks shorter in the RUTF group (p < 0.001). For the treatment of childhood MAM in Niger, RUTF resulted in a higher weight gain, a higher recovery rate, a shorter length of stay and a lower transfer rate to the I-TFC compared to a CSB pre-mix. This might have important implications on the efficacy and the quality of SFPs.